Business Process Reengineering of The New Installation Process at PDAM Tirta Agung to Improve The Company's Business Performance - Nur Alian, Galang Maftuh; Nuryana, I Kadek Dwi (Universitas Negeri Surabaya, 2025)
In increasingly complex business developments, companies are required to optimize business processes to be more effective and efficient. In addition, customer complaints are important feedback for companies to carry out evaluations to maintain their reputation in the eyes of customers. This study takes a case study on PDAM Tirta Agung, which provides clean water services in Babat District. Referring to interviews and observations, it was found that the legacy system used in the new installation business process has been running for more than four years and is considered inefficient, and time-consuming. Complaints from customers regarding the length of the installation process show that there is a need for repairs. Therefore, the Business Process Reengineering (BPR) method is proposed as a solution to improve service quality. BPR aims to implement radical changes to business processes so that companies can improve speed, accuracy, and cost efficiency, in accordance with the theory put forward by Hammer & Champy.